Set-screw loosening of spinopelvic crab-shaped fixation for a patient with vertically unstable pelvic ring fracture. (December 2022) - Yanagisawa, Yohei; Kotaki, Tomomi; Nakajima, Shun; Uesugi, Masafumi; Yamazaki, Masashi
Abstract: Spinopelvic fixation (SPF) is an effective treatment method for vertically unstable pelvic ring fractures with spinopelvic dissociations (Patel et al., 2022). A heavy container fell on a 35-year-old man who was trapped and sustained injuries. His pelvic ring fracture dislocation was identified as AO Classification 61-C2.3 with rotational and vertical unstable pelvic ring; thus, crab-shaped fixation (SPF modification) was performed (Okuda et al., 2019). The pelvic fracture was fused, and the clinical outcome was good with modified Majeed score of 96. However, set-screw loosening was observed during the postoperative course. Reports of implant failures in SPF for unstable pelvic ring fractures commonly occur. However, only a few reports have demonstrated implant failure of crab-shaped fixation. Written informed consent was obtained from the patient for publication of this case report and accompanying images.